2015
DOI: 10.1186/s12934-015-0191-y
|View full text |Cite
|
Sign up to set email alerts
|

Exchange of single amino acids at different positions of a recombinant protein affects metabolic burden in Escherichia coli

Abstract: BackgroundEscherichia coli is commonly used in academia and industry for expressing recombinant proteins because of its well-characterized molecular genetics and the availability of numerous expression vectors and strains. One important issue during recombinant protein production is the so-called ‘metabolic burden’: the material and energy normally reserved for microbial metabolism which is sapped from the bacterium to produce the recombinant protein. This material and energy drain harms biomass formation and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
84
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 51 publications
(89 citation statements)
references
References 71 publications
5
84
0
Order By: Relevance
“…In their work, a correlation between OTR reflecting the metabolic state of the culture and recombinant protein production was observed. In addition, Rahmen et al confirmed these findings for E. coli BL21(DE3) clones expressing identical proteins only differing in a single amino acid or a single codon of the heterologous protein …”
Section: Introductionmentioning
confidence: 81%
See 2 more Smart Citations
“…In their work, a correlation between OTR reflecting the metabolic state of the culture and recombinant protein production was observed. In addition, Rahmen et al confirmed these findings for E. coli BL21(DE3) clones expressing identical proteins only differing in a single amino acid or a single codon of the heterologous protein …”
Section: Introductionmentioning
confidence: 81%
“…Different frequently used T7‐based E. coli expression host strains were compared and evaluated regarding recombinant protein production of two model enzymes: a lipase A derived from B. subtilis and a 3‐hydroxybutyryl‐CoA oxidoreductase from T. thermophilus . The lipase is biochemically well characterized and under the chosen cultivation conditions predominantly expressed in inclusion bodies . It was fused to a flavin‐based fluorescent protein (FbFP) .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Glycerol is an additional energy source. It is consumed in parallel to lactose [33, 35, 36]. It was attempted to vary the time point of induction and the inducer concentration in order to influence the product formation [18, 36].…”
Section: Resultsmentioning
confidence: 99%
“…In the thioether group of IPTG (Figure 1), the sulfur atom creates a chemical bond which is non-hydrolysable by the cell, preventing the cell from degrading the inductant. IPTG has also been widely used in the recombinant processing of rhGH [7,8]. However, the toxicity of IPTG [9,10] restricted the usage of this promoter system, measuring its presence and concentration in the final products is of importance.…”
Section: Introductionmentioning
confidence: 99%